A Comparison Between Recursive Least-Squares (RLS) and Extended Recursive Least-Squares (E-RLS) for Tracking Multiple Fast Time Variation Rayleigh Fading Channel - Mahdi, Ali Salah (Al-Khwarizmi Engineering Journal, 2017)
In order to select the optimal tracking of fast time variation of multipath fast time variation Rayleigh fading channel, this paper focuses on the recursive least-squares (RLS) and Extended recursive least-squares (E-RLS) algorithms and reaches the conclusion that E-RLS is more feasible according to the comparison output of the simulation program from tracking performance and mean square error over five fast time variation of Rayleigh fading channels and more than one time (send/receive) reach to 100 times to make sure from efficiency of these algorithms.